Atypical presentation of Costeff syndrome-severe psychomotor involvement and electrical status epilepticus during slow wave sleep. (November 2015) - Carmi, Nirit; Lev, Dorit; Leshinsky-Silver, Esther; Anikster, Yair; Blumkin, Lubov; Kivity, Sara; Lerman-Sagie, Tally; Zerem, Ayelet
Abstract Background Costeff syndrome or OPA3-related 3-methylglutaconic aciduria is an autosomal recessive neurodegenerative disorder characterized by early onset optic atrophy and choreoathetosis with later onset of ataxia and spasticity. Costeff syndrome is prevalent among Iraqi Jews. Methods We describe a 5 year old girl from Syrian Jewish origin with an atypical presentation of Costeff syndrome. Results The patient presented with asymmetric optic atrophy, severe dystonia and choreoathetosis and global developmental regression at the age of 7 months; no achievement of independent walking and only minimal speech; and appearance of electrical status epilepticus during slow wave sleep in the second year of life with further deterioration. She harbors the classic mutation (c.143-1G > C) in the OPA3 gene. Conclusion Costeff syndrome may present in an atypical manner regarding the ethnic origin, clinical manifestations and co-occurrence of epilepsy. Mutations in OPA3 should be evaluated in all cases presenting with the core features of typical Costeff syndrome.